Implementation Of Knowledge Management In Small And Medium Enterprises - Rehman, Mobashar; Mahmood, Ahmad Kamil B (Journal of Knowledge Management Practice, 2010)
This study provides an insight about KM implementation in small andmediumenterprises (SMEs). SMEs from manufacturing (including manufacturing related services) and service sector (including Information and Communication Technology) have participated in the research. Paper analyzes twelve factors which are significant for the implementation of KM in SMEs. Study also discusses the reason (benefits) due to which SMEs have implemented KM or want to put KM into practice. Beside this, reasons for not implementing KM by SMEs are also part of the study. Personally administered questionnaire method was the survey instrument. Top management provided the response (feedback). Depending on the feedback provided by respondents, CSFs were prioritized base on the significant each CSF has for the implementation of KM. Reasons for implementing and not implementing KM were also prioritized.
Keywords: Knowledge management; Critical success factors; Small and medium enterprises; Pakistan; Malaysia